Pengaruh Tingkat Ekonomi Orang Tua Terhadap Prestasi Belajar Pendidikan Agama Islam Peserta Didik SD Inpres Andi Tonro - Sahal, Nur Adhayanti; Bunyamin, Andi; Hasibuddin (Journal of Gurutta Education, 2023)
The purpose of this study is to determine the economic level of parents, the learning achievement of students, and the effect of parents' economic level on the learning achievement of Islamic religious education students at SD Inpres Andi Tonro Makassar. The method used in this research is a questionnaire and documentation method. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The findings revealed: 1) Based on the results of data analysis using descriptive statistics for the economic level of parents, 6 respondents or 15.4% stated that their economic level is low, 28 respondents or 71.8% stated that the economy of their parents is included in the medium category with an income of Rp. lebih besar dari 1,500,000 to Rp. 2,500,000, while an income of Rp. lebih besar dari 2,500,000 was obtained by 5 respondents or 12.8%, stating that the economic level of their parents is in the high category. 2) Based on the results of data analysis using descriptive statistics for PAI learning achievement in students, it can be seen from the report cards of students who meet the Minimum Completeness Criteria (KKM). The average value of 82.74 was obtained in the medium category. The lowest score was 72, and the highest value was 95. 3) The results of inferential statistical analysis of the influence of parents' economic level on PAI learning achievement showed that the regression equation Y = 44.325 + 0.756 X and obtained tcount = 6,128, ttable = 2,021 because tcount lebih besar dari t table (6.128 lebih besar dari 2.021) so that Ha is accepted and Ho is rejected. As for the large influence of parents' economic level on student achievement, the results obtained are r2 = 0.504, or 50.4%, while the remaining 49.6% is explained by other variables outside of this study. Thus, it can be concluded that there is an influence of the economic level of parents on the PAI learning outcomes for students at SD Inpres Andi Tonro Makassar.